Variability in analyst decisions during the computation of numerical likelihood ratios. (18th February 2015) - Hughes, Vincent; Foulkes, Paul
Abstract : This study assesses the extent to which likelihood ratios (LRs) are affected by analyst decisions regarding the number of reference speakers, number of tokens per speaker, and degree of linguistic match between the suspect-offender and the reference data. Using F1 and F2 trajectories from spontaneous /uː/ vowels, LRs were computed against a reference set of up to 120 speakers, and between 2 and 13 tokens per speaker. LR scores proved robust when using more than 30 speakers, although validity improved as the sample size increased. Regional dialect mismatch was found to overestimate same-speaker scores by an average of one order of log10 magnitude. For different-speaker pairs, dialect mismatch generally resulted in more false hits. The results indicate that small amounts of reference data should generally be avoided, and that an awareness of the complexity of sociophonetic variation is essential in the definition of the relevant population for voice comparison.